Nigerian Rural Communities and Media Marginalization on COVID-19: Perspectives on Participatory Video - Omoera, Ph.D., Osakue Stevenson; Onyemuchara, Casmir E; Okwuowulu, Charles (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
This article examined the impact of participatory video (PV) technique in (re)educating rural dwellers on Corona virus (COVID-19) at Iva-Valley Forestry Hill Camp 1, Southeast Nigeria, with a view to generating data that could be tested or extrapolated elsewhere. It used historical-analytic, key informant interview (KII) and direct observation methods to argue that the COVID-19 pandemic/period has exposed weaknesses immanent in human institutions globally. One of such exposed interstitial gaps is the seeming weak media-link in the rural areas. This situation results from lack of electricity, non-access to reliable locally-generated news by resident community members and the lack of know-how to use mobile phones to generate media contents. Rural dwellers constitute 49.66 percent of the total Nigerian population (National Population Commission [NPC], 2018), yet media focus in Nigeria is mostly urban-driven. Having interacted and co-created a video script in Igbo with the community members through PV to determine the level of (mis)information that has permeated the community and (re)educated the rural dwellers on Corona virus and strategies to prevent its spread, the study canvassed the use of indigenous languages, diversification of media and PV techniques in the dissemination of credible information on COVID-19 in Nigeria, particularly at the grassroots